Reaction of Swiss Term Premia to Monetary Policy Surprises - Paul Söderlind (Swiss Journal of Economics and Statistics, 2010)
An affine yield curve model is estimated on daily Swiss data 2002–2009. The market price of risk is modelled in terms of proxies for uncertainty, which are estimated from interest rate options. The estimated model generates innovations in the 3-month rate that are similar to external evidence of monetary policy surprises - as well as term premia that are consistent with survey data. The results indicate that a surprise increase in the policy rate gives a reasonably sized decrease (-0.25%) in term premia for longer maturities.
Keywords: E27; E47; 330; Affine price of risk; interest rate caps; survey data